LEVELS OF HUMANITY IN RELATIONS WITH PARENTS BASED ON THE RESULTS OF DIAGNOSTICS OF PRIMARY SCHOOL STUDENTS - НоncharLiudmyla (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article is devoted to clarifying the levels of humanity in relations with parents of primary school students according to the criterion “manifestation of humane relationships in real life”. The purpose of the article is to highlight the results of pedagogical diagnostics of the behavioral and activity sphere of children of primary school age in interpersonal interaction with parents. In order to obtain reliable data on the identification of the peculiarities of the behavioral and activity sphere of primary school students in the interpersonal interaction “children-parents”, we used a complex of interrelated and complementary diagnostic methods and techniques, in particular: author’s method of solving problem situations, “lossing lottery”, statistical methods of information processing. The concept of “humane parent-child relationships” is defined as two-way dynamic subject-subject interpersonal relationships based on the synthesis of moral knowledge, motives, feelings, which determines the conscious mutual emotional and value attitude of parents and children steadily manifested in real behavior. Consequently, the author defines a three-component structure of humane relationships between parents and children of primary school age. It contains cognitive, emotional-value, and behavioral-activity components. The indicators of the behavioral and activity component were determined: the ability to show a sense of cordiality, responsiveness, care, mercy, compassion, empathy for parents; the ability to consciously analyze their decisions, actions and be responsible for their consequences; providing selfless help, showing cordiality and tact in communication. With the help of indicators of the behavioral component and a complex of interrelated and complementary diagnostic methods and techniques (the author’s method of solving problem situations, the method of “losing lottery” by M.-T. Burke-Beltran, pedagogical observation, etc.), primary students who participated in the contact stage of the experiment were conditionally divided into 3 types according to the manifestation of humane interaction of children with family members. The selfish type is distinguished by the child’s indifferent attitude towards parents and other relatives, the child’s whims, and refusal to perform household duties. The competitive type indicates a fully conscious understanding of the child that for a positive perception of it by other family members, it is necessary to be friendly, polite, and friendly with everyone. On the one hand, such a child acts based on moral and ethical norms, but on the other hand, they do not show initiative, activity, and tries to adapt to others. The humane type is characterized by the following behavioral manifestations: the child willingly enters into interpersonal contacts, treats parents and others in and out of the family with attention and respect, helps them, knows how to empathize, and tries to show humane qualities. The practical significance of the article lies in the fact that its materials can be used in the organization of educational work of general education institutions, training of teachers and pedagogical practice of students.